Directing The Agile Organisation - EVAN LEYBOURN (IT Governance Publishing, 2013)
There is nothing wrong in change, if it is in the right direction. To improve is to change, so to be perfect is to change often.’ Winston Churchill, 1925 Agile is about change; changing how you think, changing how you work, and changing the way you interact. By accepting, embracing, and shaping change, you can take advantage of new opportunities to outperform, and outcompete, in the market. While this sounds simple, change, by its very nature, is not easy. The concepts in this book change what it means to do business. ‘Agile Business Management’ is a series of concepts and processes for the day-to-day management of your organisation, regardless of industry, size or location. The end goal is to improve business adaptability, staff engagement, quality, and risk management, for the benefit of your Customers. Agile Business Management is not a quick win; it is not a ‘three-step plan’ to a ‘better business’. Agile Business Management is hard work, and requires a cultural shift from the traditional business practices of hierarchical corporate structures, customer engagement, staff management, and work processes. This book divides Agile Business Management into four domains, each requiring corresponding changes to the way your business operates. The first domain is You, the Agile Manager. Though it may seem daunting, changing the mindset and processes of management is probably the easiest change to make. It only requires an open mind and a willingness to adapt to a changing business environment. The second domain is Integrated Customer Engagement – the changing relationship and interactions between you and your Customer. Under Agile Business Management, Customers take on direct responsibility for the delivery of their Requirements. Teams and Customers work closely together, collaborating towards the desired outcomes. To be Agile, means to be flexible and adaptable to changing circumstances, and nothing changes more than your Customer’s needs. The third domain is the Structure of an Agile Organisation – how you manage your staff, the heart of your business, and how they relate to the rest of the organisation. This is a change from a traditional hierarchy, towards selfempowered individuals and Teams. One of the strengths of Agile Business Management is the focus on personal empowerment, developing engaged staff as a mechanism to drive improved customer outcomes. Whilst empowerment is difficult to define and measure, the outcomes are clear. Employees have the responsibility, accountability and authority to deliver to the Customer’s Requirements. Having examined the role of the Customer and Team, it’s time for the fourth and final domain – Work, the Agile Way. Agile Business Management uses Just-In-Time planning, and an Incremental, or Continuous, Delivery process, that allows for rapid change when scope and circumstances change. Customers work alongside the Team to shape and direct the outcomes, while the Team regularly deliver partial, though functional, products to the Customer.